The consequences of a more resource efficient and circular economy for international trade patterns A modelling assessment - Dellink, Rob (OECD Publishing, 2020)
This report investigates the effects of a resource efficiency and circular economy (RE-CE) transition on international trade flows, using the OECD's ENV-Linkages model. A global RE-CE policy package will cause secondary materials to become cheaper, while primary materials become more expensive to produce. By 2040, primary non-ferrous metals are projected to decline by 35-50%, primary iron & steel by 15% and primary non-metallic minerals by around 10%. Regional shifts in production and trade-related effects (shifts in the regional sourcing of the primary materials by the materials processing sectors) account for roughly one-third of the total reduction in materials use. The other two thirds of materials use reduction come from scale effects (reduced economic activity) and efficiency effects (reduced materials use per unit of output of the processed commodities)
Keywords: Environment; Trade